(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2004)
Jurassic rocks of the External and Internal Zones of the Betic Cordillera are widespread in the province of Murcia. Four areas are considered of special interest for stratigraphical and paleontological analysis: a) Sierra Quípar and b) Sierras Lúgar-Corque (External Subbetic), c) Sierra Ricote (Median Subbetic) and d) Sierra Espuña (Malaguide Complex). The first two contain Jurassic sections including Sinemurian-Tithonian deposits, and major stratigraphic discontinuities, containing significant cephalopod concentrations of taphonomic and taxonomic interest, occuring in the Lower-Upper Pliensbachian, Lower/Middle Jurassic and Middle/Upper Jurassic boundaries. These areas are also relevant for biostratigraphical analysis of the Middle-Upper Jurassic interval. In the Sierra de Ricote, the Mahoma section is of especial interest for the study of Lías/Dogger transition. Casa Chimeneas section constitutes the best Subbetic site for the analysis of the Lower/Upper Bajocian boundary. In the La Bermeja-Casas de Vite area, the Bajocian-Tithonian interval is well-represented, including a parastratotype of the Radiolarite Jarropa Formation. Finally, the Malvariche section in Sierra Espuña represents the best Jurassic succession of Internal Zones of the Betic Cordillera and could be considered as a reference section for this Betic Domain. In this paper a heritage evaluation has been carried out for these classical jurassic sections with the object of protecting these sites according to the legal framework prevailing in the province of Murcia.